Geopolymer/Zeolite composite materials with adsorptive and photocatalytic properties for dye removal - Pimraksa, Kedsarin (PLoS One, 2020)
This study investigated the adsorption capacities and photocatalytic activities of geopolymer-zeolite composite materials by incorporating different amounts of zeolite and TiO(2) in a geopolymer matrix for dye removal. Geopolymers with SiO(2)/Al(2)O(3) molar ratio of 2.5 were synthesized from metakaolin. The geopolymers containing zeolite and TiO(2)-doped zeolite exhibited similar behavior in terms of mineral compositions, microstructures and chemical frameworks. The compressive strength of geopolymer-zeolite composite materials decreased with increasing amount of zeolite and TiO(2)-doped zeolite (0–40 wt%) because of the increase in the porosity of composite materials. The maximum methylene blue adsorption capacity and photocatalytic efficiency of the powdered geopolymer composites with 40 wt% TiO(2)-doped zeolite was 99.1% and was higher than that of the composites with 40 wt% zeolite without TiO(2)-doping (92.5%). In addition, the geopolymer composites with TiO(2)-doped zeolite exhibited excellent stability after repeated usage as photocatalysts. The adsorption capacity and photocatalytic activity of pelletized geopolymer composites decreased because of the reduction in their specific surface area.